ChemInform Abstract: Condensation Reactions of 2‐Aminobenzohydrazide with Various Carbonyl Compounds. Issue 13 (18th March 2013) - El‐Shaieb, Kamal M.; Ameen, Mohamed A.; Abdel‐Latif, Fathy F.; Mohamed, Asmaa H.
Abstract Condensation of benzohydrazide (I) with dimedone (II) proceeds in the presence of catalytic amounts of iodine providing spiro‐quinazoline (III) whereas, phthalazino‐quinazoline (V) is obtained by simple reaction with (IV) in glacial acetic acid.